The Effect of Crocus sativus L. and Its Constituents on Memory: Basic Studies and Clinical Applications - Pitsikas, Nikolaos (Evid Based Complement Alternat Med, 2015)
Memory-related disorders are a common public health issue. Memory impairment is frequent in degenerative diseases (such as Alzheimer's disease and Parkinson disease), cerebral injuries, and schizophrenia. The dried stigma of the plant Crocus sativus L. (C. sativus), commonly known as saffron, is used in folk medicine for various purposes. Several lines of evidence suggest that C. sativus and its constituents are implicated in cognition. Here we critically review advances in research of these emerging molecular targets for the treatment of memory disorders, and discuss their advantages over currently used cognitive enhancers as well remaining challenges. Current analysis has shown that C. sativus and its components might be a promising target for cognition impairments.